Música, linguagem e a comunicação filosófica do eterno retorno em Assim falava Zaratustra - Laurici Vagner Gomes (2017)
Starting from the Nietzschean account presented in Ecce Homo that a change of a musical taste lies in the genesis of the eternal return, as it's premonitory sign, this thesis discusses the elements that involve philosophical communication of this thought in the narrative of Thus Spoke Zarathustra, with special emphasis in the sense assumed by music and lyric in the characterization of it's main character as master singer of eternal return. In this context he explores the relationship of Nietzsche with his youth masters, Schopenhauer and Wagner, observing how this relationship is implied in the configuration of the dramatic context within which this thought is communicated in the work. Finally, this thesis seeks to show how the resumption of lyric, singing and dithyramb in the characterization of Zaratustra as master of the eternal return must be observed in the light of the aesthetic reorientation seen in Nietzschean thought with the abandonment of the artist's metaphysics and the conception of philosophy that Nietzsche had designed in the last period oh this production.